Socio demographic factors and physical activity associated with overweight and obesity among Iranian adolescents - Babazekri, Leila; Juni, Muhamad Hanafiah; Mohd Zulkefli, Nor Afiah; Azman, Ahmad Zaid Fattah; Movahedi, Ariyo (Espaces Marx, 2014)

(untitled)
In recent decades, the prevalence of obesity among adolescent has risen sharply worldwide. High prevalence of overweight and obesity among adolescent has been reported in developing countries undergoing nutritional transition. Adolescents overweight and obesity usually lead to adulthood overweight and obesity and it is an important risk factor of adulthood chronic diseases such as cardiovascular diseases. The aim of this study was to investigate the prevalence of overweight and obesity and its associated factors amongst Iranian adolescents residing overseas, namely in Malaysia. Cross sectional study was conducted among 161 adolescents (84 males and 77 females) age 14 to 18 years old attending Iranian Schools in Malaysia. Validated self-administered questionnaires were employed in this study. The study found prevalence of overweight and obesity was 49.7% (male 52.4% and female 46.8%). The study also revealed that there were significant association between overweight and obesity with grade of study (χ²=19.17, p=0.02) and level of physical activity (χ²=16.15, p=0.001). Among male adolescents there were significant association with parents education (mothers’ education: X2=4.77, p=0.029, fathers’ education: X2=7.5, p=0.006), but there were no association between overweight and obesity among female adolescent with parent education (mothers’: X2=1.4, p>0.23, fathers’ education: X2=1.45, p>0.24). The study also revealed there were no significant association between overweight and obesity with family income in both genders (X2=7.5, p>0.006). The finding also showed that prevalence of overweight and obesity were high among Iranian adolescents residing overseas compare to adolescents at their homeland. There is need to address the risk factors associated with overweight and obesity among this group of adolescents.